Al Roker's recipes to live by : easy, memory-making family dishes for every occasion - Roker, Al, 1954-; Laga, Courtney Roker (Legacy Lit, 2024)
"100 joy-including dishes from the Roker family recipe box. Written and kitchen-tested by AL Roker and his daughter, professional chef Courtney Roker Laga. For all skill level, from beginner home cooks to seaoned chefs--using our favorite pantry staples. Cheerful family photos, stunning dishes that taste as good as they look, and Al's frank, witty opinions on food and cooking."--Back cover.